Phthalic acid esters in the sea-surface microlayer, seawater and sediments of the East China Sea: Spatiotemporal variation and ecological risk assessment. (April 2020) - Zhang, Ze-Ming; Yang, Gui-Peng; Zhang, Hong-Hai; Shi, Xi-Zhi; Zou, Ya-Wen; Zhang, Jing
Abstract: The spatial and temporal distribution, congener profiles and ecological risk of phthalic acid esters (PAEs) were investigated in the seawater and sediment samples from the East China Sea in spring and autumn. The average concentrations of ΣPAEs in water samples were 3.16 ± 2.16 μg L −1 in autumn and 1.63 ± 1.20 μg L −1 in spring. The ΣPAEs in sediment was much higher than that in seawater, with an average value of 7.36 ± 6.70 mg kg −1 (dw). PAEs levels in the sea-surface microlayer (SML) in spring were 3.61 ± 3.36 μg L −1, indicating that the PAEs were noticeably concentrated in the SML, with an average enrichment factor of 2.10. Among the 16 PAE congeners, di-n-butyl phthalate (DnBP), diisobutyl phthalate (DiBP), and di(2-ethylhexyl) phthalate (DEHP) were the preponderant PAEs in both sediment and seawater samples. Additionally, PAE concentrations in autumn were higher than those in spring, and this difference resulted mainly from the terrigenous input and marine transportation. The horizontal distributions of PAEs showed an opposite distribution pattern to salinity and temperature, a pattern which might be influenced by the inputs of fresh water. The vertical distributions of ΣPAEs were characterized by high concentrations in the surface waters, with a slight decrease with depth, and then an increase close to the seabed. The results of ecological risk in the water-phase showed that the level of potential risk followed the order of DEHP > DiBP and DnBP > DMP and DEP, which posed a high (DEHP), medium (DiBP and DnBP) and low (DMP and DEP) risk to the sensitive organisms, respectively. For the sediment-phase, DiBP and DnBP represented a high risk to the sensitive organisms, whereas DMP, DEP and DEHP had only a low risk. Graphical abstract: Image 1 Highlights: Sixteen PAEs were investigated in seawater and sediment samples. Concentrations of PAEs in autumn were higher than those in spring. DEHP, DnBP and DiBP are the dominant PAE congeners in the ECS. PAEs were significantly enriched in the surface microlayer. DnBP, DiBP and DEHP presented a risk to marine organisms at different levels. Abstract : Spatiotemporal variation, pollution characteristics, ecological risk of phthalate esters in the sea-surface microlayer, seawater and sediment of the East China Sea was demonstrated.